Understanding the Reduction of Porcine Epidemic Diarrhea Virus, Porcine Reproductive and Respiratory Syndrome Virus, and Seneca Valley Virus 1 RNA in Inoculated Feed and the Environment Following Thermal Processing - Olivia L. Harrison; Haley K. Otott; Jianfa Bai; Vaughn A. Hamill; Aaron Singrey; Phillip C. Gauger; Marcelo N. Almeida; Jason C. Woodworth; Charles R. Stark; Roman M. Pogranichniy; Cassandra K. Jones; Jordan T. Gebhardt; et al. (Kansas Agricultural Experiment Station Research Reports, 2023)
Pelleting of feed has been demonstrated to be an effective mitigation strategy for porcine epidemic diarrhea virus (PEDV) contaminated feed but has not been evaluated for other endemic swine viruses like porcine reproductive and respiratory syndrome virus (PRRSV) or Seneca Valley virus 1 (SVV1). Therefore, the objective of this experiment was to evaluate the efficacy of pelleting to inactivate PEDV, PRRSV, and SVV1 inoculated feed. Ten replicates were conducted in the Cargill Feed Safety Research Center at Kansas State University (K-State) using a pilot scale mixer, bucket elevator, pellet mill (including conditioner and die), and cooler. First, a virus negative batch of gestation feed was run through all equipment to simulate a commercial feed mill, then a positive batch of feed inoculated with all three viruses was run through all feed manufacturing equipment. Feed was conditioned to a minimum of 180°F with a 30 sec retention time; all feed was cooled for 10 min. Feed and environmental samples were taken from each piece of equipment following both the negative and positive batch. Samples were analyzed via PCR at the K-State Veterinary Diagnostic Laboratory. A four-room bioassay was conducted to evaluate the infectivity of the feed samples. Feed from the mixer and bucket elevator had greater quantities of SVV1, PEDV, and PRRSV RNA (P<0.05) than the other sampling locations. Similarly, environmental samples from the mixer and bucket elevator had greater SVV1 detection (P<0.05) than those collected from the conditioner, pellet die, and cooler. Pelleting reduced viral RNA (P<0.05) for all viruses in both feed and environmental samples. Although SVV1 and PEDV RNA were still detectable following pelleting, no pigs inoculated with the pelleted feed showed signs of SVV1 or PEDV clinical infection. Interestingly, PRRSV RNA was not detectable in pelleted feed samples. However, one pig showed signs of replicating PRRSV virus on d 7 of the bioassay which suggests a greater sensitivity when utilizing a bioassay compared to PCR alone. Overall, pelleting reduced the quantity of detectable viral RNA and reduced the risk of infectivity; yet small quantities of viral RNA remaining in the feed and environment following pelleting may increase the risk of re-contamination.
Keywords: viruses; feed mills; pelleting; mitigation; PEDV; PRRSV